The struggle for Iraq : a view from the ground up - Renahan, Thomas M. (Thomas Michael), 1941- (Potomac Books, an imprint of the University of Nebraska Press, 2017)
A political scientist's firsthand report on Iraq and his work with his Iraqi staff to promote democracy and fight corruption, from the days of the Coalition Provisional Authority to the present, and his recommendations for American policy-makers based on the lessons learned.